2018
DOI: 10.1007/s10461-018-2168-4
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Sexual Behavior, Substance Use and HIV Testing Among United States Men Who have Sex with Men Recruited Online, 2013 Through 2017

Abstract: The American Men's Internet Survey (AMIS) is conducted annually with 10,000 men age 15 + who have sex with men (MSM). Modeling was used with 39,863 AMIS surveys from 4 cycles between December 2013 to February 2017 to identify temporal trends in sexual behavior, substance use, and testing behavior (within 12 months preceding interview) stratified by participants' self-reported HIV status. HIV-negative/unknown status MSM had significant increases in condomless anal intercourse (CAI), marijuana use, use of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 27 publications
3
51
0
3
Order By: Relevance
“…AMIS is conducted in annual rounds with a goal of at least 10,000 complete surveys from eligible US MSM each year [8,9]. Briefly, participants are recruited each year through convenience sampling from a variety of websites and through social media applications using banner ads and email blasts to members.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…AMIS is conducted in annual rounds with a goal of at least 10,000 complete surveys from eligible US MSM each year [8,9]. Briefly, participants are recruited each year through convenience sampling from a variety of websites and through social media applications using banner ads and email blasts to members.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Public health agencies must find alternative ways to provide HIV testing while social distancing measures are in effect. Apps represent an opportunity to provide that service [9].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the American Men's Internet Survey (AMIS) found that 22% of MSM who use apps had never tested for HIV [9]. In addition, 77% of MSM who use apps wanted social or sexual networking apps to add a feature that would allow them to order an HIV home test from the app.…”
Section: Introductionmentioning
confidence: 99%
“…The methods and previous cycles' data have been previously published, including an analysis of multi-year trends [1][2][3][4]. This supplemental report updates the previous manuscript with the most current data available from AMIS (AMIS-2016).…”
Section: Introductionmentioning
confidence: 90%
“…There were 2,545 (12.36%) surveys determined to likely be from duplicate participants. Deduplication of survey responses was performed in the same manner as in previous AMIS cycles [1][2][3][4]. Among unduplicated surveys, almost twothirds (64.51%) were considered successful, i.e.…”
Section: Recruitment and Enrollmentmentioning
confidence: 99%